The experience of individuals following non-surgical management of Achilles tendon rupture in the United Kingdom – a qualitative study - Samuel Briggs-Price; Tom Yates; Jitendra Mangwani; Maneesh Bhatia; Seth O’Neill (PLoS ONE, 2026)
Objectives Despite extensive research on Achilles tendon ruptures (ATR), the lived experience of patients remains under explored. This study aimed to investigate the experiences of individuals managed non-surgically within the National Health Service (NHS). Design Qualitative study using semi-structured, one-to-one interviews. Setting NHS services in the United Kingdom providing non-surgical management for ATR. Participants Fifteen patients (mean age 54.5 years) who had sustained an ATR and were managed non-surgically. Participants were recruited from a specialist ATR clinic. Methods A stakeholder-informed topic guide was used to conduct semi-structured interviews. Interviews were audio-recorded, transcribed verbatim, and analysed using reflexive thematic analysis. Coding was undertaken independently by two researchers, with themes reviewed by the full research team. The study followed COREQ guidelines for qualitative reporting. Results Three themes were identified: (1) The experience of injury and entering the healthcare system: ‘it felt as if my whole ankle had exploded’ participants described sudden injury onset, sometimes painless, and varied understanding of treatment options; (2) The experience of non-surgical immobilisation: ‘you’re being told so much in that first session…I just couldn’t remember’ boot immobilisation was valued for mobility but challenged comfort and self-management; and (3) The rehabilitation journey: ‘it happened so unexpectedly so it can happen again’ fear and uncertainty about rehabilitation and returning to sport were common, shaping participant’s rehabilitation experience. Conclusions This study highlights how diverse ATR injury experiences, early management variability, and boot-related challenges impact recovery. Fear of re-rupture shapes rehabilitation and return to sport, emphasising the need for clearer guidance on boot use, weightbearing, and rehabilitation progression, alongside consistent healthcare professional support to optimise outcomes.